The Factors of Learner Internationalization Skills in Schools under the Authority of the Bangkok Metropolitan Administration - Chabamnet, Kornchawal; Phutiariyawat, Jantarat (Dhammathas Academic Journal, 2024)
This research endeavors to examine the explanatory factors of learner internationalization skills in schools under the authority of the Bangkok Metropolitan Administration. This study employed a quantitative methodology. A sample of 400 participants was obtained using the stratified random sampling approach, and comprised of teachers instructing students in Grades 7-12 in schools under the authority of the Bangkok Metropolitan Administration. The tools used for data collection included a rating scale questionnaire. The questionnaire was found to be couched at a reliability level between 0.60 to 1.00 by the Index of Item-Objective Congruence (IOC), and an entire confidence value of 0.995. The data analysis was conducted using statistical methods including mean, standard deviation, Kaiser-Meyer-Olkin Measures of Sampling adequacy, Bartlett's Test of Sphericity, and Exploratory Factor Analysis. The results revealed that: identifies the four key components of the internationalization of the skills of learners in schools under the authority of the Bangkok Metropolitan Administration: 1) intelligence and teamwork skills; 2) learning and innovation skills; 3) digital literacy skills; and 4) ethical collaboration skills, and a cumulative percentage of 73.005.